Improved neuron protection following cortical injury in the absence of Semaphorin4B - Sweetat, Sahar; Casden, Natania; Behar, Oded (Frontiers in Cellular Neuroscience, 2022)
Injury to the central nervous system induces neuronal cell death and astrogliosis, an astrocyte-mediated response that has both a beneficial and detrimental impact on surrounding neuronal cells. The circumstance however in which astrogliosis improves neuronal survival after an injury is not fully characterized. We have recently shown that Semaphorin4B (Sema4B) in the cortex is mostly expressed by astrocytes, and in its absence, astrocyte activation after an injury is altered. Here we find that in Sema4B knockout mice, neuronal cell death is reduced; as a result, more neurons survive near the injury site. Sema4B protein applied directly to neurons does not affect neuronal survival. In contrast, survival of wild-type neurons is increased when plated on glial culture isolated from the Sema4B knockout mice, as compared to Sema4B heterozygous cultures. Furthermore, this increased survival is also observed with conditioned medium collected from glial cultures of Sema4B knockout mice compared to heterozygous mice. This indicates that the increased survival is glial cell-dependent and mediated by a secreted factor(s). Together, our results imply that following injury, the lack of Sema4B expression in glial cells improves neuronal survival either as a result of reduced toxic factors, or perhaps increased survival factors under these conditions.